Meta-analysis of postoperative incision infection risk factors in colorectal cancer surgery - Jia, Li; Zhao, Huacai; Liu, Jia (Frontiers in Surgery, 2024)
Objective To evaluate the risk factors for postoperative incision infection in colorectal cancer, this meta-analysis aimed to identify key variables impacting infection incidence following colorectal cancer surgery. Methods Utilizing a meta-analytical approach, studies published from January 2015 to December 2022 were systematically collected and analyzed through the assessment of factors like body mass index, diabetes, albumin levels, malnutrition, and surgical duration. Results The meta-analysis of eleven high-quality studies revealed that elevated BMI, diabetes, low albumin levels, malnutrition, and extended surgical duration were associated with increased infection risk, while laparoscopic procedures showed potential for risk reduction. Conclusions This study underscores the significance of preoperative risk assessment and management in mitigating postoperative incision infections in colorectal cancer patients. The findings present actionable insights for clinicians to enhance patient prognoses and overall quality of life